Analysis of Structural Internal Forces and Stratum Deformation in Shaft Construction Using Vertical Shaft Sinking Machine - Hexige Baoyin; Zhibing Xu; Long Yu; Xu Zhang; Xiaoxiao Wang; Yang Liu (Buildings, 2025)
The use of the vertical shaft sinking machine (VSM) for shaft construction can effectively improve construction safety and efficiency. This study focused on analyzing the internal forces and deformation characteristics of a 50.3 m deep shaft constructed by the VSM method. Findings reveal that the external pressure of the shaft is positively correlated with the excavation depth, increasing as the depth grows. Pumping water inside the shaft disrupts the balance of the soil behind it, leading to a reduction in the external pressure of the shaft wall. During the excavation and sinking stage, the bottom connecting beam mainly endures compression. After water pumping, the coupling and restrictive effect between the bottom connecting beam and the shaft wall strengthens, significantly boosting the internal compressive stress. The stress states of the segments above and below the shaft vary: the upper segments are under pure compression, while the lower ones may experience uneven deformation due to multiple factors. Moreover, the cast-in-place piles and surrounding stratum show a “bulging” deformation pattern during sinking, greatly influenced by the shaft’s attitude deviation, whereas grouting at the shaft bottom and internal water pumping have minimal impact on the surrounding stratum.